2007
DOI: 10.1152/ajplung.00230.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-6 trans-signaling on the pro-remodeling phenotype of airway smooth muscle

Abstract: Effect of IL-6 trans-signaling on the pro-remodeling phenotype of airway smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…However, in our microarray experiments, this pathway is upregulated only at IT. Similar conclusions can be drawn for IL-6 signaling pathway, which has also been reported to be involved in asthma pathology (1). Indeed, in the present study, IL-6, gp130 (IL-6st), and IL-6r were found to be upregulated only in IT conditions.…”
Section: Discussionsupporting
confidence: 91%
“…However, in our microarray experiments, this pathway is upregulated only at IT. Similar conclusions can be drawn for IL-6 signaling pathway, which has also been reported to be involved in asthma pathology (1). Indeed, in the present study, IL-6, gp130 (IL-6st), and IL-6r were found to be upregulated only in IT conditions.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, HASM cells are also known to produce and release IL-6, a pleiotropic cytokine known to have proinflammatory actions in asthma (47). IL-6 is found in increased amounts in induced sputum of asthmatic patients after mast cell activation (48) and in the sputum, exhaled breath, and plasma of patients with COPD (49).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a disagreement in the literature whether HASM cells express IL-6 receptors and whether HASM cells are responsive to IL-6 alone (1,39). Expression of IL6R was first confirmed in all six cell lines of HASM cells by RNAseq at baseline and 24-h time points (data not shown).…”
Section: Kinetics Of Activation and Functional Effects Of Classical Il-6mentioning
confidence: 99%
“…ASM cells express receptors for a variety of cytokines, namely IL-13, IL-1␤, and TNF-␣ (73), and exposure of ASM cells to inflammatory cytokines results in significant changes in the expression of genes and cell functions (contraction, relaxation, secretion, migration) (9). There are conflicting reports whether ASM cells express the IL-6 receptor (1,39). Furthermore, the effects of classical IL-6 signaling and IL-6 trans-signaling in ASM have not been thoroughly investigated.…”
mentioning
confidence: 99%